Integration of a multi-directional wire arc additive manufacturing system with an automated process planning algorithm - Yuan, Lei; Pan, Zengxi; Polden, Joseph; Ding, Donghong; van Duin, Stephen; Li, Huijun (Journal of industrial information integration, 2022)
•This study developed a novel path planning algorithm for multi-directional wire arc additive manufacturing.•The automated path planning algorithm is integrated with robotic WAAM hardware to broaden its industrial applications.•A new concept, collision matrix, is proposed as a heuristic to reduce the complexity of the robotic path planning process.•The integrated WAAM system is verified through the deposition of a sample part with complex geometrical features. With the increasing demand for high productivity and low cost, the advanced manufacturing system has become more complex. It is challenging to develop an advanced manufacturing system by engineers or researchers from manufacturing engineering disciplines. To combine knowledge and skills from two or more disciplines, interdisciplinary engineering (IDE), from industrial information integration, was carried out as a promising subject for further developing advanced manufacturing systems. Recently, Wire arc additive manufacturing (WAAM) technology has attracted attention from industrial sectors due to its capability to fabricate medium-to-large scale components with low capital investment and high productivity. In addition, a variant of WAAM, called multi-directional WAAM techniques, has been developed for the direct fabrication of parts with overhanging features. The multi-directional approach can reduce the need for additional supporting structures, reducing (amongst other things) material costs, manufacturing time, and post-process machining requirements. Although the multi-directional WAAM has a great potential for practical industrial use, the process planning also becomes more complex for developing an automated system for industrial use. This paper presents a novel automated processing planning algorithm and integrates with the automated robot offline programming (AOLP) engine and WAAM hardware. The proposed system aims at planning the multi-directional WAAM process automatically. The process planning algorithm consists of four key modules relating to (a) robot motion planning, (b) initial collision processing, (c) layer sequence optimisation, and (d) weld torch pose adjustment. In the first stage, the required robot motions to deposit each layer are obtained through an AOLP engine. Then a collision matrix is generated to guide later steps of the planning process from these robot motions. After this, layer sequence optimisation is performed to eliminate collision between the robotic system and the part. If collision still exists, adjustments to the torch pose are made to avoid the remaining collision. The final chapter of this paper demonstrates the effectiveness of the proposed system via a real-world case study, where a workpiece with overhanging features was fabricated.